Increase in the negative socio-environmental impacts of urban planning legislation of Santos/SP - Ambrosio, Rafael Paulo; Carriço, José Marques (Risco - Journal of Architecture and Urbanism, 2021)
The land use and occupation act of the island area of Santos/SP, approved in 2018, significantly changed the urban indexes, making the real estate production in that area even more permissive, already shaped by the long incidence of functionalist zoning, which created a pattern of land occupation marked by dispersed verticalization, socio-spatial segregation, emptying of the central area and negative impacts on the environment and urban mobility. Thus, from a comparative analysis, this paper aimed to demonstrate that the new law reinforces old trends, expanding the construction potential in areas where the real estate market prefers to produce, increasing negative social and environmental impacts, in detriment of a sustainable and inclusive land occupation pattern.